Pengaruh Budaya Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Sebagai Variabel Mediasi pada Dinas Komunikasi, Informatika, Statistik, dan Persandian di Kota Cilegon - Titin Supini; Tata Rustandi; Angrian Permana (LPPM Politeknik Pratama, 2026)
In the digital era, enhancing employee performance in the government sector has become an urgent necessity to improve the quality of public services. The Communication, Informatics, Statistics, and Cryptography Agency (DKISP) of Cilegon City faces challenges in the form of a suboptimal work culture, varying levels of work discipline, and job satisfaction that influence employee performance. This study aims to analyze the influence of work culture and work discipline on employee performance, with job satisfaction serving as a mediating variable, at the Communication, Informatics, Statistics, and Cryptography Agency (DKISP) of Cilegon City. The research employed a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The sample consisted of 86 employees of DKISP Cilegon, selected through Slovin’s formula and proportionate stratified sampling technique. The findings reveal that work culture and work discipline have a positive and significant effect on job satisfaction. Furthermore, job satisfaction positively and significantly influences employee performance. Work culture and work discipline also exert a positive effect on performance, both directly and indirectly, through job satisfaction. The study concludes that job satisfaction mediates the influence of work culture and work discipline on employee performance, indicating that improvements in work culture and discipline will lead to more optimal performance.